Ascorbate Uptake and Retention by Breast Cancer Cell Lines and the Intracellular Distribution of Sodium-Dependent Vitamin C Transporter 2 - Citra Praditi; Stephanie M. Bozonet; Gabi U. Dachs; Margreet C. M. Vissers (MDPI AG, 2023)
Ascorbate plays a vital role as a co-factor for a superfamily of enzymes, the 2-oxoglutarate dependent dioxygenases (2-OGDDs), which govern numerous pathways in cancer progression, including the hypoxic response and the epigenetic regulation of gene transcription. Ascorbate uptake into most cells is through active transport by the sodium-dependent vitamin C transporter 2 (SVCT2). The aims of this study were to determine the kinetics of ascorbate uptake and retention by breast cancer cell lines under various oxygen conditions, and to investigate the role of SVCT2 in mediating ascorbate uptake and intracellular trafficking. Human MDA-MB231 cells accumulated up to 5.1 nmol ascorbate/106 cells, human MCF7 cells 4.5 nmol/106 cells, and murine EO771 cells 26.7 nmol/106 cells. Intracellular ascorbate concentrations decreased rapidly after reaching maximum levels unless further ascorbate was supplied to the medium, and there was no difference in the rate of ascorbate loss under normoxia or hypoxia. SVCT2 was localised mainly to subcellular compartments, with the nucleus apparently containing the most SVCT2 protein, followed by the mitochondria. Much less SVCT2 staining was observed on the plasma membrane. Our data showed that careful management of the doses and incubation times with ascorbate in vitro allows for an approximation of in vivo conditions. The localisation of SVCT2 suggests that the distribution of ascorbate to intracellular compartments is closely aligned to the known function of ascorbate in supporting 2-OGDD enzymatic functions in the organelles and with supporting antioxidant protection in the mitochondria.